Bikeshare destination choices and accessibility among disadvantaged communities. (February 2021) - Qian, Xiaodong; Jaller, Miguel
Highlights: Developed a competing destination model to estimate bikeshare destination choices. Analyzed bikeshare travel behaviors of various population segments and user types. Understanding user choices in disadvantaged areas helps design equitable systems. Users from disadvantaged areas are more sensitive to charges after free trip times. Improved accessibility fosters bikeshare demand among disadvantaged populations. Abstract: There is a lack of understanding of trip destination choices and behaviors for bikeshare users from disadvantaged communities, which are usually underrepresented in bikeshare users' profiles. Consequently, this study develops a competing destination model to analyze the spatial patterns of choice parameters of bikeshare trips. This research highlights the fact that areas with improved accessibility (i.e., the capability to access different mobility services and technologies, and/or to reach key destinations/opportunities) are more likely to attract bikeshare trips. Among user types (i.e., annual members, day-pass users), annual members from disadvantaged areas are more likely to travel longer distances to other areas that offer more services and opportunities. However, these users are more sensitive to the extra charge levied after the 30-minute grace trip time. This study provides practical suggestions towards designing equitable bikeshare systems to make the social benefits of bikeshare available to all.